2004
DOI: 10.1021/jp0376875
|View full text |Cite
|
Sign up to set email alerts
|

A DFT Study on Isomorphously Substituted MCM-22 Zeolite

Abstract: The density functional theory has been used to study the isomorphously substituted MCM-22 zeolite for the first time. The effect of the basis sets on the calculation results is discussed in details. Data of several index properties for characterizing the relative acidity of T-MCM-22 (T ) B, Al, Ga, and Fe), including proton affinity, bond length and bond angle, OH stretching frequency, and charge on the acidic proton, show that the acidity of T-MCM-22 increases in the sequence of B-MCM-22 < Fe-MCM-22 < Ga-MCM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
49
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 30 publications
9
49
0
1
Order By: Relevance
“…T3 is the most probable site for Ti IV incorporation; T7 is the next most preferred site but is not accessible to adsorbents. The distribution of Ti IV in MCM-22 zeolite is quite different from that of Al, [28][29] a situation similar to that of Ti IV and Al substitutions in MFItype zeolites. [16-17, 23-24, 26-27] Distribution of the Ti III ions: The local structures of the eight Ti III sites, taken from the optimized 49-T cluster model (Figure 1b), are shown in Figure 3.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…T3 is the most probable site for Ti IV incorporation; T7 is the next most preferred site but is not accessible to adsorbents. The distribution of Ti IV in MCM-22 zeolite is quite different from that of Al, [28][29] a situation similar to that of Ti IV and Al substitutions in MFItype zeolites. [16-17, 23-24, 26-27] Distribution of the Ti III ions: The local structures of the eight Ti III sites, taken from the optimized 49-T cluster model (Figure 1b), are shown in Figure 3.…”
Section: Resultsmentioning
confidence: 83%
“…[16][17][18][19][20][21][22][23][24][25][26][27] Recently, the Al locations in MCM-22 zeolite were studied by Corma et al and our group. [28][29][30] It was found that these ions are not equally distributed among the various T sites. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Herein, density functional calculations were employed to determine the Ti IV distribution in MCM-22 zeolite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of experimental and theoretical efforts have devoted to clarifying the acidities of M 3+ -doped zeolites [4][5][6][7][8][9][10]. Calculations of various cluster models and theoretical levels indicated that the Brönsted acidities increase in the order B < Fe < Ga < Al-doped zeolites [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Calculations of various cluster models and theoretical levels indicated that the Brönsted acidities increase in the order B < Fe < Ga < Al-doped zeolites [7][8][9][10]. Instead, the studies with incorporation of tetravalent ions (M 4+ ) lag far behind [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%